Kinetika Biodegradasi Limbah Minyak Bumi Menggunakan Biokompos - Wa Nirmala Wa Nirmala; Asri Saleh; Iin Novianty (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2015)
Kinetic study of the biodegradation petroleum waste by using biocompost was conducted to determine the concentrations of Total Petroleum Hydrocarbons (TPH) decline. It can be seen from the reaction kinetics of biodegradability by calculating the rate constant and reaction order of biodegradation of the petroleum waste. Otherwise it can be seen also from the activity of enzymes involved in the biodegradation namely enzymatic kinetics by measuring the value of Km and Vmax. Research methods are mixing biocompost and petroleum waste, measurement of pH, water content and determining the concentration of TPH at day 0, 7, 14, 21, 28 and 35. The concentrations of TPH before and after biodegradation are 11.23% and 0.54%. The results show biodegradation by using biocompost can decrease the Total Petroleum Hydrocarbons up to 95.19% within 35 days. The degradation rate is 0.502% per day while the rate constant is 0.0847 which relevant to the first-order reaction rate. The reaction kinetics of biodegradation by oxygenase enzyme show Vmax and Km value as 0.0834 and -0.9920, respectively.